2017
DOI: 10.1021/acs.iecr.7b03044
|View full text |Cite
|
Sign up to set email alerts
|

Electroplated Palladium Catalysts on FeCrAlloy for Joule-Heat-Ignited Catalytic Elimination of Ethylene in Air

Abstract: Palladium catalysts were electroplated onto Fe–Cr–Al alloy to build Joule-heat-ignition catalytic reactors for the complete oxidation of ethylene. The catalytic process involved directly passing electric currents through the alloy substrates to generate Joule heat, leading to a temperature increase in the supported catalysts and hydrocarbon ignition. The effects of alloy pretreatment and alumina washcoating on the Joule-heat-ignited catalytic performance were studied. The electroplated palladium catalyst suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The above phenomena indicate that the relative abundance of major elements in the oxide layer of stainless steel substrate can be controlled by adjusting parameters such as reaction temperature, time and oxidation atmosphere, which could promote the in-situ growth of active phase and/or improve the chemical affinity between catalyst and metal support (Duran et al 2011 ). However, it should be noted that the high-temperature oxidation process will reduce the thermal and electrical properties of the materials (Montebelli et al 2014 ), which does not facilitate the subsequent electrochemical deposition (Li et al 2017a ).…”
Section: Preparation Of Stainless Steel Catalystmentioning
confidence: 99%
See 3 more Smart Citations
“…The above phenomena indicate that the relative abundance of major elements in the oxide layer of stainless steel substrate can be controlled by adjusting parameters such as reaction temperature, time and oxidation atmosphere, which could promote the in-situ growth of active phase and/or improve the chemical affinity between catalyst and metal support (Duran et al 2011 ). However, it should be noted that the high-temperature oxidation process will reduce the thermal and electrical properties of the materials (Montebelli et al 2014 ), which does not facilitate the subsequent electrochemical deposition (Li et al 2017a ).…”
Section: Preparation Of Stainless Steel Catalystmentioning
confidence: 99%
“…Several points should also be noted during preparation: The interaction between the pretreatment and the active phase coating method should be carefully examined. Li et al ( 2017a ) electrodeposited Pd species on anodized and calcined FeCrAl-alloy, respectively. Despite the smaller particle size and better dispersion of Pd particles obtained on FeCrAl-anode, Pd/FeCrAl-cal exhibited better catalytic, Fig.…”
Section: Preparation Of Stainless Steel Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…In the area of reaction engineering, however, the literature on this type of energy transfer mechanism is scarce, with only a few papers published in the recent years. [108][109][110][111] Among other things, Pinto et al 109 have shown that Ohmic heating not only could shorten the reaction time with respect to the traditional oil bath but was also able to deliver significantly higher yields than the microwave heating for various organic synthesis reactions in water. Another interesting concept has been presented is the recent Science paper by Wismann and co-authors, 111 who proposed a new, electric resistance-heated reactor for the steam reforming of (Fig.…”
Section: Reaction Chemistry and Engineeringmentioning
confidence: 99%